2013
DOI: 10.3389/fgene.2013.00049
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diet during Pregnancy Induces Gene Expression and DNA Methylation Changes in Fetal Tissues in Sheep

Abstract: Studies in rats and mice have established that maternal nutrition induces epigenetic modifications, sometimes permanently, that alter gene expression in the fetus, which in turn leads to phenotypic changes. However, limited data is available on the influence of maternal diet on epigenetic modifications and gene expression in sheep. Therefore, the objectives of this study were to investigate the impact of different maternal dietary energy sources on the expression of imprinted genes in fetuses in sheep. Ewes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 78 publications
(93 reference statements)
4
73
0
1
Order By: Relevance
“…Interestingly, we found most of the disturbed gene expression were located in the KCNQ1 and IGF2/H19 clusters, consistent with the role of IGF2 as a major fetal growth regulator [54]. Diets of pregnant ewes containing different starch/fiber/protein portions have been shown to change the CpG methylation levels of specific imprinted genes such as IGF2R and H19 [20]. Our data also showed that despite the dramatic maternal diet changes, the allelic expression pattern was not affected, further suggesting that gene expression levels and imprinted patterns may be regulated through different epigenetic mechanisms.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, we found most of the disturbed gene expression were located in the KCNQ1 and IGF2/H19 clusters, consistent with the role of IGF2 as a major fetal growth regulator [54]. Diets of pregnant ewes containing different starch/fiber/protein portions have been shown to change the CpG methylation levels of specific imprinted genes such as IGF2R and H19 [20]. Our data also showed that despite the dramatic maternal diet changes, the allelic expression pattern was not affected, further suggesting that gene expression levels and imprinted patterns may be regulated through different epigenetic mechanisms.…”
Section: Discussionsupporting
confidence: 61%
“…Poor maternal nutrition, either over- or restricted-feeding during pregnancy [19], has been shown to cause abnormal DNA methylation and expression of a few imprinted genes, such as IGF2R and H19 in ovine fetuses [20]. NGS, however, has the power to simultaneously determine expression changes of all known imprinted genes, which has yet to be conducted in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1 produces the enzyme DNA methyltransferase, which maintains DNA methylation in newly synthesized DNA strands. 5 Animal studies [20][21][22] have shown that maternal diet can influence DNMT1 methylation/expression. For example, a choline deficiency in pregnant rats (hypo)methylates the regulatory CpGs within the DNMT1 gene, leading to its overexpression; this results in an increase of global and gene specific (IGF2) DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…These amino acids included levels of alanine, glycine, glutamate, tryptophan and tyrosine [30]. In a metabolomic profiling study of 74 obese and 67 lean individuals, a number of differences in fatty and amino acids were reported [31]. Levels of free fatty acids C14:0, C16:0, C16:1, C18:1, C20:4 remained elevated in obese as compared to lean subjects.…”
Section: Metabolomic Analysis In Obese Humansmentioning
confidence: 99%
“…Therefore, epigenetic modifications are hypothesised to be trans-generational and have been shown to be reversible whereby specific epigenetic marks can be turned on or off depending on the stimuli (Bishop et al). Most of these studies have been performed in animal models including mice [24,25], rats [26,27], Macaque [28], drosophila [29] and sheep [23,30,31]. The effects of the in utero environment on foetal programming in humans have not been well explored.…”
Section: Early Life Epigenetic Programmingmentioning
confidence: 99%